3D Navigation-guided Resection of Giant Ventral Cervical Intradural Schwannoma With 360-Degree Stabilization. Issue 5 (June 2018) - Hussain, Ibrahim; Navarro-Ramirez, Rodrigo; Lang, Gernot; Härtl, Roger
Abstract : Giant schwannomas are defined as intradural extramedullary tumors that span >2 vertebral body lengths. Although uncommon, these lesions can cause significant mass effect on the spinal cord and subsequent neurologic compromise. Gross total resection is the goal of operative intervention, however, is extremely challenging in cases where the tumor occupies a ventral, midline position within the lower cervical thecal sac. Using a representative case presentation, we describe an adult male with insidious progression of upper extremity radicular pain and paresthesias, found to have a ventral, solid/cystic C5–C7 giant schwannoma. We demonstrate the step-by-step surgical technique for an anterior approach 2-level cervical corpectomy, microsurgical resection of an intradural giant schwannoma, watertight dural closure, and lastly 360-degrees instrumented stabilization of the cervicothoracic spine. In addition we incorporate the utilization of a portable intraoperative computed tomography for stereotactic localization and 3-dimensional navigation-guided screw implantation. Finally, we discuss various preoperative, perioperative, and postoperative considerations that can have profound impact on successful outcomes. Abstract : Supplemental Digital Content is available in the text.